Modified NRTL Equation in Predicting Liquid – Liquid Equilibria - Al-Jiboury, Khalid Farhod Chasib (Nahrain University College of Engineering Journal, 2014)
The present work deals with fitting literaturedata of liquid – liquid equilibria and to obtain anew correlation for non-randomness parameter?suitable to use in NRTL activity coefficientmodel.New simple correlation is proposed formodifying the original three-parameter NRTLactivity coefficient model to make it a true twoparametermodel. The performance of theproposed expression is compared with the originalthree-parameter NRTL activity coefficient model,in correlating LLE data of binary systems, as wellas in predicting binary systems from infinitedilutionactivity coefficients and ternary systemsfrom binary data.To ensure the results had physical significance,the obtained parameters were used to predict theinfinite activity coefficients. Properties at infinitedilution are of interest as they usually indicate themaximum non-ideality of the system.The model was successfully applied tocorrelate liquid - liquid equilibria, and lowtemperature activity coefficients. A large databaseof data was collected for the investigation and itcovers a wide range of composition, temperatureand pressures. It was found that the proposed formof non-randomness parameter gave the bestresults.